IMPLEMENTASI MEDIA PEMBELAJARAN STEAM BERBASIS VIRTUAL REALITY DALAM PEMBELAJARAN MATEMATIKA DAN IMPLIKASINYA TERHADAP MINAT BELAJAR SISWA SMA - Musliman, Acep; Hermansyah, Hermansyah; Luqmanul, Hilman; Hasanudin, Januar Muhamad; Prayoga, Muhammad Reyza; Suratno, Suratno (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
ABSTRACT The low level of students’ learning interest in Mathematics and Natural Sciences (MIPA) at Senior High Schools (SMA) remains a challenge, particularly due to the dominance of conventional teaching methods and the limited use of digital technology in the learning process. This study aims to develop learning media based on the Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach integrated with Virtual Reality (VR) technology and to examine its validity, practicality, and effectiveness in enhancing students’ learning interest in MIPA. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects were Grade X senior high school students. Data were collected through learning interest questionnaires, expert validation sheets for content and media, and classroom observations. The results indicate that the VR-based STEAM learning media demonstrate a very high level of validity and are considered practical for classroom implementation. Furthermore, the use of this media is proven to be effective in increasing students’ learning interest, as reflected in higher levels of active engagement, interest in the learning materials, and curiosity during the learning process. Therefore, STEAM-based learning media integrated with Virtual Reality can be considered an innovative alternative to support MIPA learning in senior high schools in the digital era. ABSTRAK Rendahnya minat belajar siswa pada mata pelajaran Matematika dan Ilmu Pengetahuan Alam (MIPA) di Sekolah Menengah Atas (SMA) masih menjadi tantangan, terutama akibat dominasi pembelajaran konvensional dan terbatasnya pemanfaatan teknologi digital dalam proses pembelajaran. Penelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis pendekatan Science, Technology, Engineering, Arts, and Mathematics (STEAM) yang terintegrasi dengan teknologi Virtual Reality (VR) serta menguji validitas, kepraktisan, dan efektivitasnya dalam meningkatkan minat belajar siswa MIPA. Metode yang digunakan adalah Research and Development (R&D) dengan model ADDIE yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Subjek penelitian adalah siswa kelas X SMA. Data dikumpulkan melalui angket minat belajar, lembar validasi ahli materi dan media, serta observasi pembelajaran. Hasil penelitian menunjukkan bahwa media pembelajaran STEAM berbasis VR memiliki tingkat validitas yang sangat baik dan dinilai praktis untuk diterapkan dalam pembelajaran. Selain itu, penggunaan media ini terbukti efektif dalam meningkatkan minat belajar siswa, yang tercermin dari meningkatnya keterlibatan aktif, ketertarikan terhadap materi, dan rasa ingin tahu selama proses pembelajaran. Dengan demikian, media pembelajaran STEAM terintegrasi Virtual Reality dapat dijadikan sebagai alternatif inovatif untuk mendukung pembelajaran MIPA di SMA pada era digital.